MODEL-MODEL LIVING HADIS PONDOK PESANTREN KRAPYAK YOGYAKARTA - Suryadilaga, Muhammad Alfatih (Al Qalam, 2009)
This article explores the phenomenon of hadith that has become traditions of Muslim society. This study is also called â€œliving hadithâ€ defined as the religious phenomenon such as modes of conduct based on or responses to interpretation of hadith texts. By using the methods of obsevation, interview, and documents and the integrated-interconnected scientific approach, the research found that the phenomena of living hadith at Pondok Pesantren AI-Munawwir and Ali Maksum Krapyak could be classified into three traditions: oral tradition, written tradition, and practical tradition. Besides religious motivations, factors that formed these three traditions are also caused by cultural acculturation between local (Javanese) Culture and Islamic doctrine and differences of the interpretation methods on hadith texts among Muslim community.